OP0039 EFFICACY AND SAFETY OF ABATACEPT IN ACTIVE PRIMARY SJÖGREN'S SYNDROME: RESULTS OF A RANDOMISED PLACEBO-CONTROLLED PHASE III TRIAL. (June 2019) - Baer, Alan; Gottenberg, Jacques-Eric; E., William St. Clair; Sumida, Takayuki; Takeuchi, Tsutomu; Seror, Raphaèle; Foulks, Gary; Nys, Marleen; Johnsen, Alyssa; Wong, Robert; Ray, Neelanjana; Bootsma, Hendrika; et al.
Abstract : Background: Traditional DMARDs have limited efficacy in primary Sjögren's syndrome (pSS) and, so far, no biologic DMARDs are approved for its systemic treatment. Two open-label studies suggested abatacept (ABA) may have a beneficial effect on disease activity and had an acceptable safety profile in pSS. 1, 2 Objectives: To examine the efficacy and safety of ABA vs placebo (PBO) in patients (pts) with moderate-to-severe pSS. Methods: In this Phase III, double-blind, PBO-controlled study (NCT02915159 ), adult pts meeting the 2016 ACR-EULAR criteria for pSS with EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) ≥5 were randomised to receive ABA 125 mg SC weekly or PBO for 168 days (24 weeks), followed by a 197-day (365-day in Japan) open-label period of ABA treatment. All pts had a 168-day post-treatment follow-up period. Randomisation was stratified by corticosteroid (CS) and hydroxychloroquine (HCQ) use, enrolment in Japan (yes/no) and stimulated whole salivary flow (SWSF; < or ≥0.1 mL/min). The primary endpoint was mean change in ESSDAI at Day 169. Key secondary endpoints included mean changes in EULAR Sjögren's Syndrome Patient Reported Index and SWSF at Day 169. Other secondary endpoints included objective measures of eye and mouth dryness, DAS28 (CRP), patient-reported outcomes and biomarkers. Hierarchical testing for the primary and two key secondary endpoints was done to preserve overall type I error of 5%. Results: A total of 187 (ABA, 92; PBO, 95) pts were randomised and received ≥1 dose of study drug. Baseline characteristics were comparable between treatment groups: mean (SD) age was 52 (12.9) years, 95% of pts were female, 64% were white, 40% were receiving concomitant stable-dose HCQ and 25% oral CS (≤10 mg/day prednisone equivalent). Mean (SD) baseline ESSDAI score was 9.4 (4.3) (ABA, 8.7 [3.4] vs PBO, 10.1 [5.0]). At Day 169, no significant differences were seen between ABA- and PBO-treated pts for the primary or key secondary efficacy outcomes (Table 1). Applying the Benjamini–Hochberg method (with a false discovery rate of 5%) at Day 169, significant treatment differences were observed for 5/12 biomarkers (post hoc analysis) (Table 1). Serious AEs related to the study drug occurred in 3% of ABA- and 1% of PBO-treated pts. Related AEs occurred in 46% and 25% of ABA- and PBO-treated pts, respectively, but this was not enriched for any specific event and there were no new ABA safety signals. Conclusion: Despite favourably impacting biomarkers of disease activity, abatacept therapy was no better than PBO for improving the clinical measures of disease. These results do not indicate a clinical benefit of abatacept in pSS. References: [1] Meiners PM, et al. Ann Rheum Dis2014;73:1393–6. [2] Adler S, et al. Arthritis Care Res (Hoboken)2013;65:1862–8. Acknowledgement: We acknowledge the contribution of Marianne Peluso as protocol manager. Professional medical writing: Lola Parfitt, MRes, Caudex; funding: Bristol-Myers Squibb. Disclosure of Interests: Alan Baer Consultant for: I have no conflicts of interest within the past 12 months. In 2017, I served on advisory boards for Novartis and AbbVie., Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, E. William St. Clair Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Takayuki Sumida Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K., Raphaèle Seror Grant/research support from: Pfizer, Consultant for: Bristol-Myers Squibb, Pfizer, Amgen, Eli Lilly, Roche, Celgene, GlaxoSmithKline, MedImmune, Gary Foulks Shareholder of: Stock: TearLab, Inc, Consultant for: Lexitas PharmaServices, Kala, Bristol-Myers Squibb, Aldeyra, Allysta, Clemencia, Aurinia, Hovione, Sight Sciences, Noveome, Tarsus, Marleen Nys Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Alyssa Johnsen Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Robert Wong Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Neelanjana Ray Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Hendrika Bootsma Grant/research support from: Unrestricted grants from Bristol-Myers Squibb and Roche, Consultant for: Roche, Bristol-Myers Squibb, Novartis, Medimmune, Union Chimique Belge, Speakers bureau: Bristol-Myers Squibb, Novartis